Host–guest interactions between p-sulfonatocalix[4]arene and p-sulfonatothiacalix[4]arene and group IA, IIA and f-block metal cations: a DFT/SMD study - Nikolova, Valya K.; Kirkova, Cristina V.; Angelova, Silvia E.; Dudev, Todor M. (Beilstein Journal of Organic Chemistry, 2019)
The molecular recognition in aqueous solution is extremely important because most biological processes occur in aqueous solution. Water-soluble members of the calix[n]arene family (e.g., p-sulfonato substituted) can serve as model systems for studying the nature and manner of interactions between biological receptors and small ions. The complex formation behavior of water-soluble p-sulfonatocalix[4]arene and thiacalix[4]arene and group IA, IIA and f-block metal cations has been investigated computationally by means of density functional theory computations in the gas phase and in aqueous environment. The calculated Gibbs free energy values of the complex formation reaction of these ligands with the bare metal cations suggest a spontaneous and energy-favorable process for all metal cations in the gas phase and only for Na+, Mg2+, Lu3+ cations in water environment. For one of the studied cations (La3+) a supramolecular approach with explicit solvent treatment has been applied in the study of the effect of metal hydration on the complexation process. The La3+ binding to the p-sulfonatocalix[4]arene host molecule (now in the metal’s second coordination shell) is still exergonic as evidenced by the negative Gibbs free energy values (ΔG1 and ΔG78). The combination of implicit/explicit solvent treatment seems useful in the modeling of the p-sulfonatocalix[4]arene (and thiacalix[4]arene) complexes with metal cations and in the prediction of the thermodynamic parameters of the complex formation reactions.
Keywords: complex formation; DFT; group IA; IIA and f-block metal cations; macrocycles; p-sulfonatocalix[4]arene; p-sulfonatothiacalix[4]arene